2018
DOI: 10.4236/jct.2018.91003
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-Induced Tumour Lysis Syndrome in Gastric Adenocarcinoma with Diffuse Liver Metastases: A Case Report

Abstract: Tumour Lysis Syndrome (TLS) is an important oncological emergency case which is often found together with haematological malignities and, much less often, with solid tumours. While TLS seen in solid tumour cases usually develops following a cytotoxic chemotherapy and its prognosis is poor. We present the case of a 60-year-old man with gastric adenocarcinoma with diffuse liver metastases (image shows diffuse liver metastatic lesions) and high serum LDH levels, who developed TLS after systemic chemotherapy. With… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Search results yielded 8 additional cases of TLS in gastric adenocarcinoma (Table 3). 4-11 Of these, 4 have been spontaneous TLS 4-7 and the other 4 were chemotherapy-induced. 8-11 Including our patient, the mean age at presentation was 55 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Search results yielded 8 additional cases of TLS in gastric adenocarcinoma (Table 3). 4-11 Of these, 4 have been spontaneous TLS 4-7 and the other 4 were chemotherapy-induced. 8-11 Including our patient, the mean age at presentation was 55 years.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] Of these, 4 have been spontaneous TLS 4-7 and the other 4 were chemotherapy-induced. [8][9][10][11] Including our patient, the mean age at presentation was 55 years. All 9 patients were male.…”
Section: Discussionmentioning
confidence: 99%
“…We did a review of literature, and we summarized the 9 reported cases of TLS in gastric adenocarcinoma in Table 2. [1][2][3][4][5][6][7][8][9] Of these, 4 cases were spontaneous TLS, and the other 5 were chemotherapy-induced, with only 1 of the 5 cases being FOLFOX-induced. The mean age at presentation was 55 years and all 9 patients were males.…”
Section: Tumor Lysis Syndrome: a Rare Complication Of Metastatic Gast...mentioning
confidence: 99%